2021
DOI: 10.3390/ani12010025
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters for Growth, Ultrasound and Carcass Traits in New Zealand Beef Cattle and Their Correlations with Maternal Performance

Abstract: Research has shown that enhancing finishing performance in beef cows is feasible; however, any adverse impact of selection strategies for finishing performance on the performance of the maternal herd should be taken into account. The aim of this research was to examine the inheritance of growth, ultrasound and carcass traits in finishing beef cattle and to evaluate their correlations with maternal performance traits. Data were collected from a nationwide progeny test on commercial New Zealand hill country farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
2
5
0
1
Order By: Relevance
“…We confirmed the adequate health status of all animals on the Spanish farm at all time points, with all metabolites falling within physiological ranges [37][38][39][40][41][42][43][44][45][46], although one report indicated that Wagyu cattle may reduce feed intake during summer due to heat stress [47]. Therefore, this type of production system, under Spanish climatic conditions with no restriction of exercise and with a locally sourced, high-olein diet, is appropriate for rearing and fattening Wagyu and Wangus animals.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…We confirmed the adequate health status of all animals on the Spanish farm at all time points, with all metabolites falling within physiological ranges [37][38][39][40][41][42][43][44][45][46], although one report indicated that Wagyu cattle may reduce feed intake during summer due to heat stress [47]. Therefore, this type of production system, under Spanish climatic conditions with no restriction of exercise and with a locally sourced, high-olein diet, is appropriate for rearing and fattening Wagyu and Wangus animals.…”
Section: Discussionsupporting
confidence: 52%
“…The BHB level was significantly higher in the ACL animals than in the two other breeds at weaning, perhaps reflecting a higher level of stress in the ACL animals, which can reduce their feed intake [71]. The BHB level in Japanese animals was slightly higher at other time points than at weaning, but it was always within the physiological range [37][38][39][40][41][42][43][44][45][46]. We found no significant differences in NEFA levels between the ACL and Wagyu animals, which was similar to the finding of another study that compared Holstein and Wagyu [65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimativas moderadas de herdabilidade para AOL, EG e P8 foram similares as relatadas na literatura para bovinos Nelore, variando entre 0,17 a 0,34 (6,17,19,20) . Estimativas moderadas de herdabilidade para MAR e PCQ também foram relatadas por Gordo et al (34) , Tonussi et al (35) e Weik et al (36) avaliando bovinos Nelore. Os resultados obtidos indicaram que parte da variação dessas características é atribuída aos efeitos aditivos e que as características de carcaça podem responder à seleção genética, modificando a composição corporal em um curto espaço de tempo se a pressão da seleção genética for intensa (20) .…”
Section: Discussionunclassified